Effect of fattening length, sex and feather colour on growth and fattening performance in native turkish geese - Mustafa Saatçi; Cavit Arslan; Yücel Ünal; Muammer Tilki; Ali Rıza Aksoy (Eurasian Journal of Veterinary Sciences)
Aim: Study was undertaken to determine the intensive fattening performance of native Turkish geese and to underline the effects of fattening length, sex and feather colour on fattening performance. Materials and Methods: Total 145 daily goslings were used in the experiment. Birds divided into four groups according to their feather colour in each fattening (10 and 12 weeks) period. Birds with wing tags were individually weighed and all the birds were weighted weekly according to their groups. Results: There was not any statistical significance between the fattening groups (10 and 12 weeks) in term of weekly liveweight (p>0.05). Effects of both feather colour and sex on liveweight have started at the fifth week and continued until at the end of the fattening periods (p<0.05). The highest liveweight gain was observed in yellow geese while the lowest liveweight gain was in piebalds. Obtained results provided additional information on the growth pattern of native Turkish geese reared under the intensive condition. Yellow feather coloured geese reached to greater live-weights than the others. Conclusion: Observed lower liveweight gain and increasing food consumption do not allow the breeders to fatten the native Turkish geese under the intensive condition after 9-10 weeks of age.